Physical damage caused by bamboo (Guadua weberbaueri Pilg.) in tree species and implications for logging in Bamboo Open Rainforest in eastern Acre (Research, Society and Development, 2022)
The state of Acre, in the Brazilian Amazon, has 18 forest typologies, eight of which have bamboo (Guadua spp.) as the main or secondary floristic element in their understory. Few studies were able to detail changes in forest typologies in which bamboo is the dominant species, caused by bamboo. The present work evaluated the extent and detailed the types of damage caused by bamboo (Guadua weberbaueri Pilg.) in arboreal individuals found in a fragment of Open Rain Forest with bamboo (G. weberbaueri) dominant in the understory located in the eastern region of Acre and discuss the implications for logging. For this purpose, three plots measuring 50 x 100 m were installed along a 1000 m transect, 300 m apart. Bamboo caused damage in 32% of the individuals evaluated (DBH ≥ 2 cm). The most frequent types of damage were “shoring” (44.74% of the total sampled) and “breakage” (37.55%). The confirmation that the presence of bamboo causes damage to arboreal individuals, compromising the density, volume and quality of their bole, has implications for the sustainable exploitation of wood in forests in which it is present and will demand the development of practices management to mitigate the negative impacts observed.